Comparison of antibacterial effect of methanolic and hydro-alcoholic ziziphus spina-christi extract with 2.5% sodium hypochlorite on enterococcus faecalis: an in vitro study - Akam Saeidi; Mahmoud Reza Hamidi; Abolfazl Davoodabadi; Elham Mahmoudi; Soraya Khafri; Zahra Nikouee Rad (Caspian journal of dental research, 2018)
Introduction: Root treatment will not be successful, without a proper root canal irrigation with less disadvantages and antibacterial effect. The aim of this study was to compare antimicrobial effect of cedar extract and 2.5%NaOCl on E. faecalis. Materials & Methods: In disk diffusion test, a standard suspension of E. faecalis (ATCC 29212) was cultured on plate and different concentrations (0.05, 0.15, 0.25, 0.35, 0.45 g/ml) of methanolic or hydro-alcoholic extracts, 2.5% NaOCl and physiologic serum (as negative control) were infused on paper disks. The inhibition zone measured after 48 h. In microdilution test, serial dilution of methanolic and hydro-alcoholic extracts, 2.5% NaOCl and physiologic serum in 1:2 proportion was performed in Brain Heart Infusion (BHI) culture medium. Then, standard suspension of E. faecalis was added to each well of micro plate. Data were analyzed using ANOVA. Results: Hydro-alcoholic and methanolic extracts had antibacterial effect on E. faecalis. Inhibition zone of 2.5% NaOCl was significantly higher than that of other extracts (p<0.001). In microdilution test, E. faecalis bacterium was sensitive to both hydro-alcoholic and methanolic extracts but it was more sensitive to 2.5% NaOCl. Conclusion: Totally, 2.5% NaOCl had the highest antibacterial effect on E.faecalis followed by hydro-alcoholic and methanolic extracts. NaOCl is an effective irrigant in root treatment until the studies like this can find a good alternative for it.